Analisis Kualitas Butir Soal Tes Multiple Choice Mata Pelajaran Ekonomi pada Siswa Kelas XI IPS SMA Kristen Aprian Damer - Berbiru, Sanci; Tomasoa, Theodora Florence; Ubra, Franklin William (Universitas Pattimura, 2024)
Improving the quality of education requires periodic evaluation of assessment tools, such as multiple-choice tests commonly used in secondary schools. This study aims to analyze the quality of multiple-choice test items for Economics subject among eleventh-grade IPS students at Aprian Damer Christian Senior High School, Southwest Maluku Regency. The research adopts a mixed-method descriptive qualitative and quantitative approach, utilizing documentation techniques on test items, answer keys, and students’ answer sheets. The analysis focuses on item difficulty, discrimination power, and distractor function using standard calculation formulas. The results indicate that many test items do not yet meet the criteria for high quality, especially regarding the proportion of item difficulty and the effectiveness of distractors. These findings highlight the need for ongoing professional development for teachers in designing effective test items as evaluation tools. It is recommended that teachers ensure balanced item construction, improve suboptimal items, and conduct item quality analysis before using them in formal assessments to guarantee that evaluation results truly reflect students' competencies